Digital transformation of the Algerian Banking Sector: Opportunities and challenges under Law No. 23-09 - Boussouf, Azzeddine (International journal of economic perspectives, 2025)
This article explores the digital transformation of the banking sector in Algeria, focusing on the implementation of Law No. 23-09. It analyzes how this law promotes digital banks and payment service providers (PSPs), addressing both opportunities and challenges. The study examines the implications of digitalization on financial inclusion, regulatory frameworks, and technological infrastructure. By comparing Algeria’s initiatives with international best practices, the article offers insights into the potential impact of digital banking on the Algerian economy and presents recommendations for a successful transition.